Changing prevalence patterns in endoscopic and histological diagnosis of gastritis? Data from a cross-sectional Central European multicentre study - Wolf, Eva Maria; Plieschnegger, Wolfgang; Geppert, Michael; Wigginghaus, Bernd; Höss, Gabriele M.; Eherer, Andreas; Schneider, Nora I.; Hauer, Almuthe; Rehak, Peter; Vieth, Michael; Langner, Cord (Digestive and Liver Disease, 2014)
Background and aims: Traditionally, Helicobacter infection is considered to be the most common cause of gastritis. In the cross-sectional Central European histoGERD trial, we assessed the prevalence of different types of gastritis, correlating histological and endoscopic diagnoses. Methods: A total of 1123 individuals participated in an observational multicentre study. Endoscopists classified individuals as positive or negative for gastritis and rendered the putative cause. Pathologists evaluated biopsy specimens based upon the Updated Sydney System. Results: Histological diagnosis of gastritis was made in 639 (56.9%) participants. In all, 210 (18.7%) individuals were diagnosed with Helicobacter gastritis, 215 (19.1%) with post Helicobacter gastritis, 234 (20.8%) with reactive gastropathy, 26 (2.3%) with autoimmune gastritis, and 6 (0.5%) with focally enhanced gastritis related to Crohn's disease. In 46 out of 639 (7.2%) individuals diagnosed with gastritis, combinations of different histological subtypes were noted the most common being reactive gastropathy and post Helicobacter gastritis. Endoscopic diagnosis of gastritis was made in 534 (47.6%) individuals. Conclusions: Reactive gastropathy was more common than active Helicobacter gastritis, and the majority of cases attributable to Helicobacter infection were no longer ongoing, i.e. post Helicobacter gastritis. Agreement between histological and endoscopic diagnoses was better in reactive gastropathy than in Helicobacter gastritis. © 2014 Editrice Gastroenterologica Italiana S.r.l.
CRIS-Team Scopus Importer:2025-03-05
Keywords: Epidemiology; Gastropathy; Helicobacter gastritis; Intestinal metaplasia; Reflux gastritis